Microtus abbreviatus Miller 1899 ... - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus abbreviatus Miller 1899 Microtus abbreviatus Miller 1899, Proc. Biol. Soc. Wash., 13: 13. Type Locality: USA, Alaska, Bering Sea, Hall Isl. Vernacular Names: Insular Vole. Synonyms: Microtus fisheri Merriam 1900. Distribution: Hall and St. Matthew Isls, Bering Sea (Alaska, USA). Conservation: IUCN – Data Deficient. Discussion: An insular relative of M. miurus of the Alaskan mainland, generally retained as a species (Fedyk, 1970; Jones et al., 1997; Rausch and Rausch, 1968) but separate status questioned (Conroy and Cook, 2000 a). Also see accounts of M. gregalis and M. miurus. ... : Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 990, DOI: 10.5281/zenodo.7316535 ...